Distinguished identification of halal and non-halal animal-fat gelatin by using microwave dielectric sensing system. Issue 1 (1st January 2019) - Sin, Kit Yeng; Sin, Mun Chong
Abstract: Halal has been a long-disputed issue due to the reason of its complexity consequently of swift advancement in innovation and technology. Gelatin plays a vital role in modern food processing as it has been used in many food preparations and is commonly used to make the pharmaceuticals capsule these days. In this work, various types of animal fat will measure dielectrically to distinguish them for the development of the detection system. This project applied the measurement of reflection coefficient by using the high-temperature probes. These probes use the principle of microwave method and allow the measurement to be made in a fast and non-destructive way. For this project, the high-temperature probe is used to measure the sample of animal fat for instance chicken, beef and pork fat. The fresh animal fat was used and the moisture content of the animal fat was manipulated by using the oven-drying technique. The different levels of moisture content inside the fat will affect the measurement value of reflection coefficient as the moisture content will change the dielectric properties of the animal fat. The measurement of reflection coefficient was made with a network analyzer in the frequency range of 0.2 GHz to 20 GHz. From the experimental result, it can be concluded that pork fat shows distinguishable trend compared with chicken and beef fat which perform similar trend in variation of reflection coefficient (|S11 |), dielectric constant (έ) and dielectric loss (ἔ) throughout the frequency range from 0.2 GHz to 20 GHz.